Folk taxonomy and traditional uses of common bean (Phaseolus vulgaris L.) landraces by the sociolinguistic groups in the central region of the Republic of Benin - Laura Estelle Yêyinou Loko; Joelle Toffa; Arlette Adjatin; Ahouélété Joel Akpo; Azize Orobiyi; Alexandre Dansi (BMC, 2018)
Abstract Background Common bean (Phaseolus vulgaris L.) is an important grain legume crop grown in the central region of the Republic of Benin. However, its production declined in recent years to the extent that its diversity is being threatened with extinction. Understanding the folk nomenclature and taxonomy, as well as use values that allow its maintenance in Beninese agricultural system, is a prerequisite to develop efficient strategies for its conservation. Knowing that each sociolinguistic group develop various uses and traditional knowledge for their crop genetic resources, we hypothesized that enhancement of farmers' livelihood, thanks to the use values of common bean landraces, differ from one sociolinguistic group to another and contribute to their conservation in the traditional agriculture of central Benin. Methods Hundred and one common bean producers belonging to seven sociolinguistic groups selected through 23 villages of the region under study were surveyed. Data were collected through participatory research appraisal tools and techniques (individual interviews and direct observation) using a semi-structured questionnaire. Folk nomenclature and taxonomy of common bean, local uses, and factors affecting them were investigated. Results Across the seven sociolinguistic groups surveyed in the study area, five common bean generic names and 26 folk varieties corresponding to 12 landraces have been recorded. Folk nomenclature and taxonomy were mainly based on seeds' coat color. The present study has revealed five common bean use values in the study area (food, medicinal, commercial, fodder, and mystic-religious), which are influenced by sociolinguistic groups. Leaves, roots, and seeds of three common bean folk varieties are used by surveyed farmers for disease treatment. Nine common bean folk varieties are considered by farmers as magical plants which have supernatural properties while several taboos for deities' followers regarding Séssé landrace are inventoried across sociolinguistic groups. Level of education and age of respondents influence positively and significantly medicine and mystical-religious uses of common bean respectively while commercial use is positively influenced by age and negatively by gender. Conclusions Traditional values associated with common bean landraces in the central region of the Republic of Benin increase their chance of survival in the farming systems. Socio-demographic characteristics of respondents which influence common bean use values must be taken into account in future programs of conservation. However, an assessment of diversity and analysis of distribution of extend of common bean landraces in the study area is a necessity for the development of an efficient strategy of conservation of this genetic resource.